2009
DOI: 10.1073/pnas.0906498106
|View full text |Cite
|
Sign up to set email alerts
|

Live imaging of rapid chromosome movements in meiotic prophase I in maize

Abstract: The ability of chromosomes to move across the nuclear space is essential for the reorganization of the nucleus that takes place in early meiotic prophase. Chromosome dynamics of prophase I have been studied in budding and fission yeasts, but little is known about this process in higher eukaryotes, where genomes and chromosomes are much larger and meiosis takes a longer time to complete. This knowledge gap has been mainly caused by difficulties in culturing isolated live meiocytes of multicellular eukaryotes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
113
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(121 citation statements)
references
References 35 publications
(63 reference statements)
6
113
2
Order By: Relevance
“…Prophase chromosome movements in maize appear more complex in comparison to other species, as they include both coordinated chromatin rotations as well as movements of individual chromosome segments. In contrast to maize, only uncoordinated movements of individual chromosomes or chromosome segments are seen in budding yeast, while only coordinated movements of the entire chromatin have been reported in fission yeast (Schizosaccharomyces pombe) and rat (Rattus norvegicus) spermatocytes (Sheehan and Pawlowski, 2009).…”
Section: Chromosome Motility In Meiotic Prophase Imentioning
confidence: 99%
See 4 more Smart Citations
“…Prophase chromosome movements in maize appear more complex in comparison to other species, as they include both coordinated chromatin rotations as well as movements of individual chromosome segments. In contrast to maize, only uncoordinated movements of individual chromosomes or chromosome segments are seen in budding yeast, while only coordinated movements of the entire chromatin have been reported in fission yeast (Schizosaccharomyces pombe) and rat (Rattus norvegicus) spermatocytes (Sheehan and Pawlowski, 2009).…”
Section: Chromosome Motility In Meiotic Prophase Imentioning
confidence: 99%
“…In plants, studies using intact live anthers of maize showed that meiotic chromosomes exhibit complex and stage-specific motility patterns in zygotene and pachytene (Sheehan and Pawlowski, 2009). During zygotene, short chromosome segments adjacent to chromosome ends exhibit robust shortrange movements, while movements of interstitial chromosome segments are more restrained.…”
Section: Chromosome Motility In Meiotic Prophase Imentioning
confidence: 99%
See 3 more Smart Citations